2006
DOI: 10.1097/01.mlg.0000214866.32050.2e
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory versus Portable Sleep Studies: A Meta‐Analysis

Abstract: Home sleep studies provide similar diagnostic information to laboratory polysomnograms in the evaluation of sleep-disordered breathing but may underestimate sleep apnea severity. The lower cost of home sleep studies makes it a viable screening tool for patients with suspected OSA; however, these lower costs are partially offset by the higher rate of inadequate examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 18 publications
4
43
0
1
Order By: Relevance
“…Data loss for the present PM study of 10.4% from patient-related failures and 3.7% from technical failures compares favorably to previous studies, with a recent meta-analysis reporting an overall 14.6% of poor recordings. 33 In a recent targeted case finding study in the primary care setting (using the same PM device), 7% technical failure was reported. 44 Consistent with our findings, the most common reasons cited for data loss were patient-related issues and partial or complete absence of data.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data loss for the present PM study of 10.4% from patient-related failures and 3.7% from technical failures compares favorably to previous studies, with a recent meta-analysis reporting an overall 14.6% of poor recordings. 33 In a recent targeted case finding study in the primary care setting (using the same PM device), 7% technical failure was reported. 44 Consistent with our findings, the most common reasons cited for data loss were patient-related issues and partial or complete absence of data.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…This degree of underestimation is consistent with previous PM data, which showed that on average AHI PM was 10% lower than AHI PSG. 33 The cases most likely to be missed (false negatives) are those with mild OSA since the inherent underestimation of the PM may recategorize mild cases below the diagnostic threshold for OSA (AHI < 5 events/h). False negative rates can be as high as 17% 10 in unattended PM studies leading to the recommendation that PMs be used to rule in OSA in the setting of a high pretest probability.…”
Section: -11mentioning
confidence: 99%
“…[112][113][114] Our findings confirm those of previous reviews, health technology assessments and clinical practice guidelines based on earlier evidence of portable monitor use in the diagnosis of sleepdisordered breathing. [25][26][27][31][32][33][34][35][36][37][38][39]115 These reviews concluded that level 3 devices are useful in the diagnosis of obstructive sleep apnea in patients with a high pretest likelihood of having moderate to severe forms of the condition. The American Academy of Sleep Medicine and Canadian Sleep Society/Canadian Thoracic Society guidelines recommend that portable sleep studies be provided under the direction of health professionals with accreditation in sleep medicine and as part of a comprehensive assessment.…”
Section: E48mentioning
confidence: 99%
“…We determined our date limit based on several previous Canadian and American assessments that examined the earlier literature. [31][32][33][34][35][36][37][38][39][40] Study selection Two reviewers independently screened titles and abstracts to identify possible studies for inclusion. All studies comparing level 3 with level 1 sleep tests involving adults were included if they reported on either diagnostic accuracy parameters or management after testing (Appendix 2, available at www .cmaj .ca /lookup /suppl /doi :10 .1503 /cmaj.130952/-/DC1).…”
Section: Literature Searchmentioning
confidence: 99%
“…La polisomnografía es sin lugar a dudas el procedimiento gold estandar para definir la presencia o ausencia de enfermedad (1,4-10) pero desde la publicación original de Neil Douglas el año 1992 (11) hasta la fecha se han trabajado múltiples equipos simplificados con menos sensores y que tienen como objetivo documentar o rechazar el diagnóstico de trastornos respiratorios del sueño; específicamente el SAHS (12)(13)(14)(15)(16).…”
Section: Introductionunclassified